1997
DOI: 10.2337/diacare.20.11.1683
|View full text |Cite
|
Sign up to set email alerts
|

U.K. Prospective Diabetes Study 27: Plasma lipids and lipoproteins at diagnosis of NIDDM by age and sex

Abstract: Plasma lipids and lipoproteins at diagnosis of NIDDM by age and sex U.K. PROSPECTIVE DIABETES STUDY GROUP OBJECTIVE-To compare fasting plasma lipids and lipoproteins in male and female patients at diagnosis of NIDDM and to examine age and sex differences in lipid concentrations. RESEARCH DESIGN A N D METHODS-Cross-sectional study of fasting plasma total cholesterol, LDL cholesterol, HDL cholesterol, and triglyceride in 2,139 male and 1,574 female white patients, aged 25-65 years, at diagnosis of NIDDM.RESULTS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(9 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Probably reason lies in two bare facts; first possibility suggest that due to increase of triglycerides (>2.25 mmol/L) with low LDL and HDL ratio [23-30] and second possibility is the weight gain with no-exercise behavior and poor diet control [11-13,17,24,31-34]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Probably reason lies in two bare facts; first possibility suggest that due to increase of triglycerides (>2.25 mmol/L) with low LDL and HDL ratio [23-30] and second possibility is the weight gain with no-exercise behavior and poor diet control [11-13,17,24,31-34]. …”
Section: Discussionmentioning
confidence: 99%
“…Although the causes of increased cardiovascular risks in both type 2 diabetes and metabolic syndrome are multifactorial, an atherogenic lipid profile characterized by elevated triglycerides and low levels of high-density lipoprotein (HDL) cholesterol are few major modifiable factor contributing progressively in cardiovascular risk [17]. Level of low-density lipoprotein (LDL) cholesterol typically is not elevated and in fact may even be below average.…”
Section: Introductionmentioning
confidence: 99%
“…However, dyslipidemia may correlate more directly with cardiovascular complications [2], and mechanistic evidence is emerging regarding the greater lipocentric versus glucocentric nature of CVD risk in patients with type 2 diabetes [7,18]. Insulin resistance is central to the pathogenesis of type 2 diabetes and contributes to dyslipidemia [17].…”
Section: Characteristics and Mechanisms Of Lipoprotein Abnormalities mentioning
confidence: 99%
“…However, significantly fewer patients with type 2 diabetes had HDL-C and TG at optimal levels compared with patients without type 2 diabetes (Figure 2) [27]. Consistent with the data from NHANES 1999-2000, data from the United Kingdom Prospective Diabetes Study (UKPDS) in 3713 newly diagnosed patients with type 2 diabetes reported that HDL-C levels were lower (by 9% [men] and 23% [women]) while TG levels were 50% higher in patients with type 2 diabetes than in nondiabetic patients; LDL-C values were similar (for males but higher in females) between those with and without type 2 diabetes [2]. As the pattern of elevated lipids was more pronounced in females, it was suggested to contribute to the greater cardiovascular risk in females compared with males [2].…”
Section: The Prevalence Of Dyslipidemia In Association With Type 2 DImentioning
confidence: 99%
See 1 more Smart Citation